The Effect of Temperature on the Spread of the Coronavirus in the U.S. (2020)
I investigate whether the cross-sectional data on cumulative (symptomatic) cases of coronavirus in the 48 contiguous states of the U.S. at the end of March 2020 provide any evidence that the rate of transmission of the virus declines at higher temperatures. Average temperatures in March varied from 30 to 71 degrees Fahrenheit in the 48 states. Controlling for other relevant factors, including population density and the availability of testing, I find no evidence that a higher average temperature in a state reduced the incidence of cumulative cases/capita of the virus in the state. These results provide no indication that seasonal increases in temperature will cause the coronavirus epidemic to disappear in the summer.